Spatial distribution of benthic macrofauna in the Central Arctic Ocean. - Vedenin, Andrey; Gusky, Manuela; Gebruk, Andrey V; Kremenetskaia, Antonina; Rybakova, Elena; Boetius, Antje (PANGAEA, 2018)
Permanent sea-ice cover and low primary productivity in the mostly ice-covered Central Arctic ocean basins result in significantly lower biomass and density of macrobenthos in the abyssal plains compared to the continental slopes. However, little is known on bathymetric and regional effects on the macrobenthos diversity. This study synthesizes new and available macrobenthos data to provide a baseline for future studies of the effects of Arctic change on macrofauna community composition in the Arctic basins. Samples collected during three expeditions (in 1993, 2012 and 2015) at 37 stations on the slope of the Barents and Laptev Seas and in the abyssal of the Nansen and Amundsen Basins in the depth range from 38 m to 4381 m were used for a quantitative analysis of species composition, abundance and biomass. Benthic communities clustered in five depth ranges across the slope and basin. A parabolic pattern of species diversity change with depth was found, with the diversity maximum for macrofauna at the shelf edge at depths of 100–300 m. This deviates from the typical species richness peak at mid-slope depths of 1500–3000 m in temperate oceans. Due to the limited availability of standardized benthos data, it remains difficult to assess if and how the significant sea-ice loss observed in the past decade has affected benthic community composition. The polychaete Ymerana pteropoda and the bryozoan Nolella sp. were found for the first time in the deep Nansen and Amundsen Basins.
Environmental conditions, macrozoobenthos abundance and biomass from three expeditions to the Central Arctic Ocean